ROLA AMERYKAŃSKIEGO TELEWANGELIZMU W KSZTAŁTOWANIU POSTAW CHRZEŚCIJAŃSKICH ZWYKŁEGO CZŁOWIEKA - Krauze, Łukasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The televangelism shapes a religion consciousness of Christians living in the United States of America. Specially protestants who are involved in the evangelical movement. Success of the televangelism is rooted in a public availability, an accessible method of interpretation of God’s Word and pop culture connections. This paper unveils how the American televangelism influences on the religious consciousness of “the common man” and show a reason of an attractiveness of the televangelism though a modern world struggles with a faith’s crisis.